Early stressful experiences are associated with reduced neural responses to naturalistic emotional and social content in children - Park, Anne T.; Richardson, Hilary; Tooley, Ursula A.; McDermott, Cassidy L.; Boroshok, Austin L.; Ke, Adrian; Leonard, Julia A.; Tisdall, M. Dylan; Deater-Deckard, Kirby; Edgar, J. Christopher; Mackey, Allyson P. (Developmental cognitive neuroscience, 2022)
How do children’s experiences relate to their naturalistic emotional and social processing? Because children can struggle with tasks in the scanner, we collected fMRI data while 4-to-11-year-olds watched a short film with positive and negative emotional events, and rich parent-child interactions (n = 70). We captured broad, normative stressful experiences by examining socioeconomic status (SES) and stressful life events, as well as children’s more proximal experiences with their parents. For a sub-sample (n = 30), parenting behaviors were measured during a parent-child interaction, consisting of a picture book, a challenging puzzle, and free play with novel toys. We characterized positive parenting behaviors (e.g., warmth, praise) and negative parenting behaviors (e.g., harsh tone, physical control). We found that higher SES was related to greater activity in medial orbitofrontal cortex during parent-child interaction movie events. Negative parenting behaviors were associated with less activation of the ventral tegmental area and cerebellum during positive emotional events. In a region-of-interest analysis, we found that stressful life events and negative parenting behaviors were associated with less activation of the amygdala during positive emotional events. These exploratory results demonstrate the promise of using movie fMRI to study how early experiences may shape emotional, social, and motivational processes. •We related a novel movie fMRI paradigm to children’s early stressful experiences.•Higher SES related to greater activity in OFC to parent-child interaction movie events.•Negative parenting related to blunted activity to positive emotional movie events.•Movie fMRI is useful for studying children’s naturalistic socioemotional processing.